Implementasi Konsep SMART pada Perancangan Interior Coffee Cafe & Roastery Di Surabaya - Laurencia Angela; Hedy Constancia Indrani; Grace Setiati Kattu (Intra, 2019)
The impact of current era development causes people's lifestyles to change, especially among youth, therefore many entrepreneurs make this phenomenon as an opportunity to open a business, such as a coffee cafe. Currently coffee cafe is not only becoming a place to make transactions, but many people also go to the café to work, gather, chat, discuss and others. SMART Coffee Café and Roastery is a place to accommodate the needs of the society, not only as a café in general, in this café visitors can experiment in making their own coffee. The purpose of this design is to design a Coffee Café and Roastery that provides education to society in Indonesia, especially in Surabaya about coffee through the design application. The design method used is adopting design thinking scheme according to Carol Dweck with 10 stages which are Discovery, Observe, Emphatize, Leverage Stories to Discover Insights, Frame and Reframe, Ideate, Decide, Prototype, Validate your Idea, Iterate. Benefits that can be felt by visitors or the community are they will feel more comfortable and calm in the café, and will be able to get to know more about history and various types of coffee through the design that’s applied.